Reverse engineering for obsolete single layer printed circuit board (PCB) - Che Mat, Ruzinoor; Azmi, Shahrul; Daud, Ruslizam; Zulkifli, Abdul Nasir; Ahmad, Farzana Kabir (2006)
One of the backbones in electronic manufacturing industry is the printed circuit board (PCB). The recent rapid growth in electronics devices, results escalating in the production number of the PCBs. For electronic equipment and appliances which are PCB based, new generations of PCB's are produced to suit the requirements of new products.This development can lead to waste and inefficiency when perfectly serviceable electronic components and appliances have to be scrapped because of the unavailability of spare PCB's from the Original Equipment Manufacturer (OEM) or are already obsolete. This paper proposed a novel framework for reverse engineering of obsolete single layer PCB.Equivalent PCB's which can be used as spares will be reproduced utilizing this new framework. This framework involves several steps, such as data acquisition, image processing, CAD editing, PCB fabrication and circuitry testing and analysis. Each stage of the framework and the functionality evaluation of the reproduced PCB will be discussed in detail in following sections.